Differences in opioid prescriptions between subjects with and without intellectual and developmental disability during the COVID-19 pandemic. - Kim, Jaewhan; Abbinanti, Alan; Ben-Umeh, Kenechukwu C.; Sanchez, Joseph; Waitzman, Norm; Jones, Kyle (Journal of Substance Use, 2026)
Objective: This study compared opioid prescription rates between individuals with and without intellectual and developmental disability (IDD) in Utah from 2019 to 2021. Methods: Using the 2019–2021 Utah All Payer Claims Database (APCD), we analyzed adults aged 18–62 in 2019, matching those with IDD to those without. We examined opioid prescription frequency, total days of supply, and average morphine milligram equivalents (MME) per prescription each year. Linear random-effects models and negative binomial regression with a random intercept were used. Results: In 2020, individuals with IDD received 40% fewer opioid prescriptions (IRR = 0.60, p < 0.01) and 43% fewer in 2021 (IRR = 0.57, p < 0.01). They also had 1.10 fewer days of supply in 2020 (β = -1.10, p < 0.01) and 1.77 fewer in 2021 (β = -1.77, p < 0.01). MME per prescription was 1.51 lower in 2020 (β = -1.51, p < 0.01) and 1.46 lower in 2021 (β= − 1.46, p < 0.01). Conclusions: Despite an overall increase in opioid prescriptions during the pandemic, individuals with IDD received fewer prescriptions, less medication, and lower MME. Future research should examine whether fewer opioid prescriptions of subjects with IDD may indicate potential disparity or benefits.